Aksi pemberdayaan dan edukasi kader tuberkulosis dalam deteksi kasus tuberculosis, serta deteksi dini hipertensi dan diabetes mellitus di Palembang - Pasaribu, Rouly; Ahmad, Zen; Andriani, Linda; Sudarto, Sudarto; Rasyid, Ahmad; Fathurrachman, Alif; Setyorini, Dwi Indira (Fakultas Kedokteran Universitas Sriwijaya, 2023)
Pulmonary tuberculosis is a global health problem. According to the 2022 world tuberculosis report, Indonesia is ranked 2nd in the world with an estimated 969,000 cases. The number of cases of pulmonary tuberculosis found and reported was only 443,235berculosis report, Indonesia is ranked 2nd in the world with an estimated 969,000 cases. The number of cases of pulmonary tuberculosis found and reported was only 443,235. There are still around 500,000 cases that have not been discovered and reported. Co-morbidities such as hypertension and diabetes mellitus are also diseases that are often encountered but are often ignored when they are still in their early phases. Hypertension and diabetes mellitus in pulmonary tuberculosis patients can adversely affect treatment outcomes. Tuberculosis cadres can play an important role in increasing pulmonary tuberculosis case detection and the early detection of comorbidities. Therefore, it is necessary to increase the effectiveness of tuberculosis cadres in Palembang in order to achieve an increase in case detection and comorbidities. Through the tuberculosis cadre organization, Sriwijaya Healthy Society, 15 tuberculosis cadres were given counseling with enrichment on case finding and early detection of hypertension and diabetes mellitus. Through questionnaires before and after counseling, an increased understanding of tuberculosis case detection and early detection of hypertension and diabetes mellitus was obtained, with an average score before 56.7 and an average score after 91.3. Simulated training on the early detection of hypertension and diabetes mellitus was also carried out so that the cadres could apply it to the community.